Синдром эмоционального выгорания в деятельности работников дежурно-диспетчерских служб МЧС Республики Беларусь - Komkova Е.; Smirnova И. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article represents the results of the empirical research on the syndrome of emotional burnout in relation to dispatchers of rescue services as representatives of extreme professions. There is analysis of the gender aspect of the studied phenomenon, the factors influencing its manifestation and the degree of expression, as well as connection with empathyand alexithymia, as personality characteristics.